Slippery dealn ; Diabetes for life ; On Wings of song - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Deals with the sale of Petro corporation to ARAMCO; the diabetes and its awareness programs and the classical guitarists, Acoustic Alchemy.
Slippery dealn (20 min.) -- Diabetes for life (15 min.) -- On wings of song (15 min.).
VHS.
Keywords: Petron Corporation (Philippines) Acoustic Alchemy; Diabetes -- Philippines